The effect of selective interactions at the interface of polymer-oxide hybrid solar cells - Canesi, E; Binda, M; Abate, A; Guarnera, S; Moretti, L; D'Innocenzo, V; Kumar, R; Bertarelli, C; Abrusci, A; Snaith, H; Calloni, A; Brambilla, A; et al. (2012)
The working mechanisms of excitonic solar cells are strongly dominated by interface processes, which influence the final device efficiency. However, it is still very challenging to clearly track the effects of inter-molecular processes at a mesoscopic level. We report on the realization of polymer-based hybrid solar cells made of prototypical materials, namely, poly(3- hexylthiophene) (P3HT) finely infiltrated in a TiO2 scaffold, with power conversion efficiency exceeding 1%. A step-change improvement in the device performance is enabled by engineering the hybrid interface by the insertion of an appropriate molecular interlayer. An unprecedented set of characterization techniques, including time-resolved optical spectroscopy, X-ray photoemission spectroscopy, positron annihilation spectroscopy and atomistic simulations, allows us to rationalize our findings. We show that a suitable chemical structure of the interlayer molecule induces selective intermolecular interactions, and thus a preferential surface energetic landscape and morphological order at the interface which consequently drives a strong improvement in charge generation and a decrease in recombination losses. © 2012 The Royal Society of Chemistry.